Spectocurrency: War Spectacle in Social Media - Vera Syamsi (k@ta: A Biannual Publication on the Study of Languange and Literature, 2024)
Social media has been influential and important in people’s life as a place for socializing, finding entertainment and - nowadays- information. People share various images and videos – or spectacles- through the platforms, with Tik Tok and Instagram as two of the most popular platforms. This research highlights and analyzed war spectacles created by the President of Ukraine and a Ukrainian university student on those platforms that were aimed at raising people’s awareness and empathy to the sufferings of the country and hopefully support their fight against Russia’s invasion, using semiotics concept, and proves that spectacles do have power to move people and generate reaction that can eventually cause expected changes, or spectocurrency.